Capitation-Based Financing Hampers the Provision of Preventive Services in Primary Health Care - Sándor, János; Kósa, Karolina; Papp, Magor; Fürjes, Gergő; Kőrösi, László; Jakovljevic, Mihajlo; Ádány, Róza (Frontiers in Public Health, 2016)
Mortality caused by non-communicable diseases has been extremely high in Hungary which can largely be attributed to not performed preventive examinations (PE) at the level of primary health care (PHC). Both structures and financial incentives are lacking which could support the provision of legally defined PEs. A Model Programme was launched in Hungary in 2012 to adapt the recommendations for PHC of the World Health Organization. A baseline survey was carried out to describe the occurrence of not performed PEs. A sample of 4320 adults representative for Hungary by age and gender was surveyed. 12 PEs to be performed in PHC as specified by a governmental decree were investigated and quantified. Not performed PEs per person per year with 95% confidence intervals were computed for age, gender, and education strata. The number of not perfomed PEs for the entire adult population of Hungary was estimated and converted into expenses according to the official reimbursement costs of the National Health Insurance Fund. The rate of service use varied between 16.7% to 70.2%. There was no correlation between the unit price of examinations and service use (r=0.356; p=0.267). The rate of not performed PEs was not related to gender, but older age and lower education proved to be risk factors. The total number of not performed PEs was over 17 million in the country. Of the 31 million EUROs saved by not paying for PEs, the largest share was not spent on those in the lowest educational category. New preventive services offered in the reoriented PHC model programme include systematic and scheduled health examination health promotion programmes at community settings; risk assessment followed by individual or group care, and/or referral and chronic care. The Model Programme has created a pressure for collaborative work, consultation and engagement at each level, from the GPs and health mediators up to the decision making level. It channeled the population into preventive health services shown by the fact that more than 80% of the population in the intervention area has already participated in the health status assessment.